Utilization of Complementary Therapy to Reduce Anxiety in Prospective Acceptors of Long-Term Contraceptive Methods - Maulinda, Amanda Via; Ni’amah, Siti; Marlinawati, Iin Tri (Newinera Publisher, 2025)
Family Planning is a government program to control population growth which has an impact on high maternal and child mortality rates. 1. The number of long-term contraceptive users in Indonesia is very low. Anxiety is one of the factors that influences the low number of contraceptive users.2 Complementary therapy is a non-pharmacological and non-conventional therapy to reduce anxiety 3. The aim of this study was to utilize complementary therapy to reduce anxiety in prospective family planning acceptors so as to increase the number of long-term contraceptive users. This type of research is pre-experimental with one group pretest-posttest design without using a control group. Respondents in this study were 30 prospective long-term contraceptive acceptors at the Jakenan Health Center, Pati, Indonesia. The anxiety measurement tool in this study used the HARS (Hamilton Anxiety Rating Scale). Data analysis used the Wilcoxon test. The results of the study showed that the provision of complementary therapy (yoga and husband's assistance) with intervention 2-4 times for 1 week with a total of 30 respondents was proven to reduce anxiety levels with a pre-test value of 21.5 (moderate anxiety) and a post-test of 10 (no anxiety). Hypothesis test results (p = 0.000 <0.05). Complementary yoga therapy accompanied by a husband has benefits in reducing the level of anxiety of prospective long-term contraceptive acceptors.